Study of the Use of Augmented Reality Technology in Improving the Learning Experience in the Classroom - Wahyuanto, Eko; Heriyanto, Heriyanto; Hastuti, Sri (Westscience Press, 2024)
The use of Augmented Reality (AR) technology in education has become an intriguing research topic in recent years. This study aims to explore the use of AR in enhancing the learning experience in classrooms. A literature review method is employed to analyze various approaches, benefits, challenges, and future prospects of AR in the educational context. Findings indicate that AR holds great potential in enhancing student engagement and conceptual understanding but faces challenges in infrastructure and teacher training. Therefore, investments in AR infrastructure development and adequate training for educators are suggested to maximize the benefits of this technology in classroom learning. Further research is also needed to explore broader applications of AR in education.